The Kiandra leek orchid is the previously presumed extinct mignonette leek orchid (Orchidaceae; Orchidoideae): evidence from morphological comparisons - Ayre, Bronwyn M.; Hayashi, Tobias; Phillips, Ryan D.; Reiter, Noushka (Phytotaxa, 2021)
Prasophyllum morganii (Orchidaceae), the mignonette leek orchid, was first collected from a single population in the subalps of Victoria, Australia, in 1929 but has not been collected since 1933. A morphologically similar leek orchid, P. retroflexum, was described in 2000 from Kosciuszko National Park, New South Wales, Australia. We measured 51 morphological traits on 14 field collected and 13 herbarium specimens of P. retroflexum, and six historical herbarium collections of P. morganii. In addition, we conducted a comparison of the types of both species with the field and herbarium specimens. Multivariate analyses were undertaken using 35 characters, and an ordination performed on range-standardised data. Results show no morphological differences between specimens identified as P. morganii and P. retroflexum, and we conclude they are conspecific.